Trend of mortality due to oral malignancy and risk factors predisposed to the brazilian population (Research, Society and Development, 2022)
Objective: To analyze the epidemiological and temporal profile of mortality from malignant oral neoplasm and its relation to risk factors to the Brazilian population, from 2000 to 2019. Methods: Observational study of mortality from Malignant Oral Neoplasm (100mil) and socioeconomic aspects, lifestyle and clinical aspects in Brazil, between 2000 and 2019. Results: There was an increase in all regions, in the South (1.4-2.5), Southeast (1.4-2.3), Northeast (0.7-1.8), Central-West (0.6-1.5) and North (0.3-1.1), especially in the state of Espírito Santos (44.8/100mil), and 0.1% of the municipalities with higher mortality in São Paulo. To the socioeconomic profile, South, Southeast and Midwest present the best indicators (income and HDI), however, inadequate lifestyle: sedentary lifestyle (24.9%), alcoholism (29.7%), smoking (15.3%) and overweight (64.4%) in the South; to the clinical aspects, presenting higher mortality rates in men (47.1/100000), between 40-59 years (106.9/100000), with no family history (58.3%), smokers (81.6%) and stylists (69.3%), with primary site of mouth tumor (21%), grade IV (52.9%) and multiple therapeutic protocols (26.8%). Conclusion: There was an increase in mortality, especially among males, over 40 years of age, smokers and alcoholics, which can infer their greater exposure to risks linked to gaps in prevention, diagnosis and treatment in Brazil.